IDENTIFIKASI EKTOPARASIT PADA IKAN BELUT RAWA (Synbranchus bengalensis) DI UNIT PEMBENIHAN RAKYAT (UPR) YOSUA DISTRIK SENTANI KABUPATEN JAYAPURA - Ikanubun, Marcela (STIPER Santo Thomas Aquinas Jayapura, 2023)
Ectoparasites can cause large numbers of deaths in fish. The effects of ectoparasites on fish (as hosts) in the form of mechanical damage, nutrient uptake and toxic effects can reduce fish stock density and reduce fish quality due to defects. Eels are a freshwater fishery commodity with quite high economic value. The aim of this research is to determine the types of ectoparasites that attack Swamp Eels (Synbranchus bengalensis) and to determine the condition of water quality during research in tarpaulin ponds at the Yosua People's Nursery Unit (UPR) in Hawaii, Sentani District, Jayapura Regency; The research lasted for 3 months, namely March to May 2023. Sampling was carried out at the